2010
DOI: 10.1258/ebm.2009.009209
|View full text |Cite
|
Sign up to set email alerts
|

Acute circuit-resistance exercise increases expression of lymphocyte agouti-related protein in young women

Abstract: Exercise-induced leukocytosis and lymphocytosis is accompanied by up-regulation and down-regulation of hundreds of genes in white blood cells (WBCs). Agouti-related protein (AgRP) is an orexigenic peptide secreted predominantly from the arcuate nucleus in the hypothalamus. AgRP affects feeding behavior and plays a role in energy and glucose homeostasis and adiposity. The purpose of the study was to determine effects of circuit resistance exercise (CRE) (9 exercises, 25 s per exercise) at different intensities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…Thus, the characterization and understanding of the immune responses may aid to future design and dose-response prescriptions of RT based on additional physiological variables, rather than just neuromuscular and metabolic parameters. As demonstrated in previous studies, leucocytosis observed immediately after the end of the RT sessions are represented mainly by the increases in neutrophils, lymphocytes and monocytes, respectively, while training loads, rest intervals and the methods can influence the magnitude of this response (Nieman et al, 2004;Mayhew et al, 2005;Ghanbari-Niaki et al, 2010;Paulsen et al, 2010). As demonstrated in previous studies, leucocytosis observed immediately after the end of the RT sessions are represented mainly by the increases in neutrophils, lymphocytes and monocytes, respectively, while training loads, rest intervals and the methods can influence the magnitude of this response (Nieman et al, 2004;Mayhew et al, 2005;Ghanbari-Niaki et al, 2010;Paulsen et al, 2010).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Thus, the characterization and understanding of the immune responses may aid to future design and dose-response prescriptions of RT based on additional physiological variables, rather than just neuromuscular and metabolic parameters. As demonstrated in previous studies, leucocytosis observed immediately after the end of the RT sessions are represented mainly by the increases in neutrophils, lymphocytes and monocytes, respectively, while training loads, rest intervals and the methods can influence the magnitude of this response (Nieman et al, 2004;Mayhew et al, 2005;Ghanbari-Niaki et al, 2010;Paulsen et al, 2010). As demonstrated in previous studies, leucocytosis observed immediately after the end of the RT sessions are represented mainly by the increases in neutrophils, lymphocytes and monocytes, respectively, while training loads, rest intervals and the methods can influence the magnitude of this response (Nieman et al, 2004;Mayhew et al, 2005;Ghanbari-Niaki et al, 2010;Paulsen et al, 2010).…”
Section: Discussionmentioning
confidence: 72%
“…In this context, studies can be found which have investigated the acute responses and chronic adaptations to the immune system in response to specific RT methods, such as single set (Pizza et al, 2001), multiple sets (Nieman et al, 2004;Simonson & Jackson, 2004;Mayhew et al, 2005;Paulsen et al, 2010) and circuit (Ghanbari-Niaki et al, 2010). Interestingly, no further studies have been designed to investigate acute immune responses to a tri-set RT session using three exercises for the same muscle group with no rest between them (Voight et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoglycemia caused during exercise also results in high response to stress and aassociated immunosuppression 4 . The circulation of white cells in the blood rapidly increases with exercise 5 . However, the training effect on the immune function depends on the intensity and the kind of exercise practiced 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of physical activity in various patterns on different physiological systems, particularly blood cells, has been clearly investigated (1)(2)(3). Like any physiological tissue, blood does not provide the same response concerning every exercise, either.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the essential role of white blood cells (WBC) in the immune system as well as their capability of gene expression due to one or several nuclei, a number of studies have focused on the effect of physical activities and exercise (2,9,10). McCarthy et al (11) found that exercising on an ergometer for 30 minutes with 48%-84% Vo2 max could increase the average number of WBC, and the number of lymphocytes and neutrophils also increased by 117%.…”
Section: Introductionmentioning
confidence: 99%